KREATIFITAS PEMBUATAN PETA TIMBUL DI SD ISLAM AL-HIKMAH GADANG MALANG - Siti Halimatus Sakdiyah; Rahaju Rahaju (Dedication : Jurnal Pengabdian Masyarakat, 2018)
Problems faced by partners in the field such as governance to the process of learning in the classroom and assessment techniques. In the learning process is not uncommon teachers experience control dlam deliver abstract material to the concrete, due to lack of availability of instructional media. Innovation and creativity of teachers in designing and developing props from used materials combined with easily accessible materials such as nails, wires, plywood, paints, glue etc. are all available in building stores, so play based learning can be improved. Evidently the teachers still have not used the old newspapers that exist in the vicinity. The dedication to the community conducted by the team aims to improve the innovation and creativity of the teachers of Al Hikmah Islamic Elementary School Gadang Malang, in order to design and make props from old newspapers processed into pulp and then mixed with white cement and glue then attached to the plywood already in the drawing map sketch. Methods used in community service in the form of training, workshops and mentoring so as to produce props in the form of embossed maps. The results obtained from the activities of dedication in SD Islam Al-Hikmah Gadang Malang, as follows: 1) The existence of the spirit of work of the teachers, especially when teaching in the classroom, thus increasing the activity and motivation of students in the learning process. 2) There is a positive working atmosphere between teachers while teaching in the classroom and more confident. 3) The existence of props products in the form of emergent maps created by the participants during the training and mentoring